Proclamation to the people: nineteenth-century Mormonism and the Pacific Basin frontier - Maffly-Kipp, Laurie F.; Neilson, Reid Larkin (Univ. of Utah Press, 2008)
Pacific basin frontier -- Nineteenth-century Mormonism and the Pacific Basin frontier : an introduction / Reid L. Neilson and Laurie F. Maffly-Kipp -- Eastward ho! American religion from the perspective of the Pacific Rim / Laurie F. Maffly-Kipp -- Americas -- The rise and decline of Mormon San Bernardino / Edward Leo Lyman -- Hoping to establish a presence : Parley P. Pratt's 1851 mission to Chile / A. Delbert Palmer and Mark L. Grover -- A providential means of agitating Mormonism? : Parley P. Pratt and the San Francisco press in the 1850s / Matthew J. Grow -- Polynesia -- Looking West : Mormonism and the Pacific world / Laurie F. Maffly-Kipp -- Mormon missionary wives in nineteenth-century Polynesia / Carol Cornwall Madsen -- Life at Iosepa, Utah's Polynesian colony / Tracey E. Panek -- Australasia -- The gathering of the Australian saints in the 1850s / Marjorie Newton -- The Mormon message in the context of Maori culture / Peter Lineham -- Nineteenth-century Pakeha Mormons in New Zealand / Marjorie Newton -- Asia -- Meetings and migrations : nineteenth-century Mormon encounters with Asians / Reid L. Neilson -- Anodyne for expansion : Meiji Japan, the Mormons, and Charles Legendre / Sandra C. Taylor -- Race, space, and Chinese life in late-nineteenth-century Salt Lake City / Michael J. Lansing